Common Characteristics of Women Who Kill In the Context of Abuse: A Content Analysis of Case Files. Issue 1 (1st February 2023) - Scott, Samantha; Geffner, Robert; Stolberg, Ronald; Sirikantraporn, Skultip
ABSTRACT: This study examined common characteristics in women who killed an intimate partner or family member in the context of abuse by using qualitative content analysis on 10 archival case files. Major (>80% of participants) and minor themes (60–79% of participants) revealed the majority of participants killed their abuser in their private home with a firearm. They were most often diagnosed with Posttraumatic Stress Disorder (PTSD), Depression, and/or Alcohol Use Disorder. On the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), most of participants had clinically elevated Scale 2 (D), Scale 4 (Pd), and Scale 8 (Sc). They also had high rates of previous interpersonal violence experiences and had often sought help from police, although they experienced unhelpful outcomes. Overall, the participants demonstrated it was not just one single event affecting their psychological functioning, behaviors, and views of the world. Rather, these women had complex histories with a series of extremely traumatic and life-altering events before they engaged in an extreme act of violence in response to or to escape the prolonged abuse they endured.